The corrosion promoting mechanism of Aspergillus niger on 5083 aluminum alloy and inhibition performance of miconazole nitrate. (November 2020) - Zhang, Tiansui; Wang, Junlei; Zhang, Guoan; Liu, Hongfang
Highlights: Aspergillus niger significantly reduces the pH of medium and sharply accelerates the corrosion of aluminum alloy. High-performance liquid chromatography analysis confirms that oxalic acid is the major ingredient of the metabolites of Aspergillus niger . The oxalic acid produced by Aspergillus niger participates in the cathodic process of aluminum alloy corrosion. Miconazole nitrate is found to well inhibit the growth of Aspergillus niger . Abstract: The corrosion behavior of 5083 aluminum alloy in the medium with Aspergillus niger and the inhibitory effect of miconazole nitrate (MN) were studied. High-performance liquid chromatography analysis confirmed that oxalic acid was the major ingredient of the metabolites of Aspergillus niger, which was responsible for the severe corrosion of aluminum alloy. According to weight loss test, the inhibition efficiency of MN against the corrosion of aluminum alloy caused by A. niger in culture medium reached 90% at 20 mg/L. The results herein demonstrate that MN possesses a considerable potential for preventing the microbiologically influenced corrosion caused by fungus.